Boron deficiency alters cytosolic Ca2+ concentration and affects the cell wall components of pollen tubes in Malus domestica. (19th December 2018) - Fang, K. F.; Du, B. S.; Zhang, Q.; Xing, Y.; Cao, Q. Q.; Qin, L.
Abstract: Boron (B) is essential for normal plant growth, including pollen tube growth. B deficiency influences various physiological and metabolic processes in plants. However, the underlying mechanism of B deficiency in pollen tube growth is not sufficiently understood. In the present research, the influence of B deficiency on apple ( Malus domestica ) pollen tube growth was studied and the possible regulatory mechanism evaluated. Apple pollen grains were cultured under different concentrations of B. Scanning ion‐selective electrode technique, fluorescence labelling and Fourier‐transform infrared (FTIR) analysis were used to detect calcium ion flux, cytosolic Ca 2+ concentration ([Ca 2+ ]cyt), actin filaments and cell wall components of pollen tubes. B deficiency inhibited apple pollen germination and induced retardation of tube growth. B deficiency increased extracellular Ca 2+ influx and thus led to increased [Ca 2+ ]cyt in the pollen tube tip. In addition, B deficiency modified actin filament arrangement at the pollen tube apex. B deficiency also altered the deposition of pollen tube wall components. Clear differences were not observed in the distribution patterns of cellulose and callose between control and B deficiency treated pollen tubes. However, B deficiency affected distribution patterns of pectin and arabinogalactan proteins (AGP). Clear ring‐like signals of pectins and AGP on control pollen tubes varied according to B deficiency. B deficiency further decreased acid pectins, esterified pectins and AGP content at the tip of the pollen tube, which were supported by changes in chemical composition of the tube walls. B appears to have an active role in pollen tube growth by affecting [Ca 2+ ]cyt, actin filament assembly and pectin and AGP deposition in the pollen tube. These findings provide valuable information that enhances our current understanding of the mechanism regulating pollen tube growth.